AL-ASH’ARI AND HIS CONCEPT OF TAWHID - H.M.A. Tihami (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 1996)
Al-Ash’ari and His Concept of Tawhid